Porous nitrogen-doped carbon-immobilized bimetallic nanoparticles as highly efficient catalysts for hydrogen generation from hydrolysis of ammonia borane. Issue 45 (14th October 2015) - Guo, Lingling; Gu, Xiaojun; Kang, Kai; Wu, Yanyan; Cheng, Jia; Liu, Penglong; Wang, Tianshu; Su, Haiquan
Abstract : High-performance hydrogen generation from hydrolysis of ammonia borane has been achieved over porous nitrogen-doped carbon-immobilized bimetallic nanoparticles. Abstract : Two N-doped carbon materials, N-doped Vulcan XC-72 carbon labelled as NXC and graphite carbon nitride labelled as C3 N4, were selected as supports to prepare a series of bimetallic AuM (M = Co, Ni) nanoparticles (NPs) using three different reduction ways towards mixed metal ions AuCl4 − and M 2+, and then the as-synthesized supported bimetallic AuM NPs were used as catalysts for hydrolytic dehydrogenation of ammonia borane (NH3 BH3 ). All the catalysts exhibited high dispersion and small size of bimetallic NPs; however, they exhibited remarkably different catalytic activities featuring total turnover frequency (TOF) values from 6.4 to 42.1 molH2 molcat −1 min −1 . Among all the catalysts, the NXC-immobilized AuCo NPs through in situ synthesis using NaBH4 and NH3 BH3 as reductants exhibited the highest activity with a total TOF value of 42.1 molH2 molcat −1 min −1, which was among the highest values for Co-based catalysts ever reported for hydrolytic dehydrogenation of NH3 BH3 . This remarkably enhanced activity may be attributed to the synergistic effect of the N-doped NXC support and AuCo NPs and the resulting highly efficient activation of N–B bond in NH3 BH3 . In addition, the AuCo catalysts showed good recyclability, demonstrating that they had high stability/durability.